ANALISIS KARAKTERISTIK BRIKET ARANG DENGAN VARIASI TEKANAN KEMPA PEMBRIKETAN - Rany Puspita Dewi; Trisma Jaya Saputra; Sigit Joko Purnomo (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2022)
Biomass is often considered as a material that is lacking or even uneconomical. Biomass that is abundantly available in Indonesia is sawdust and coconut shell waste. This number has not been used maximally, this is because both wastes tend to be disposed of directly into the environment and can cause environmental pollution. Briquetting technology is one of method which can be implemented to increase the added value by producing briquettes. Many factors affect the quality of briquettes, one of which is the pressure of the briquette press. The pressure of the briquette press affects the durability and cohesiveness of briquettes. The aim of this research was to specify the effect of compression pressure on calorific value, ash content, and water content of briquettes. The research was conducted by varying the briquetting compression pressure, namely 1500 psi, 2000 psi, and 3000 psi. It has been done by several main stages, namely the carbonization process, the manufacture of charcoal briquettes, and test analysis. Charcoal briquettes have an average heating value of 6386.377 cal/g, 1.136% moisture content, and 6.659% ash content at a compression pressure of 1500 psi. At a compression pressure of 2000 psi, charcoal briquettes have an average heating value of 6672.601 cal/g, 1.110% moisture content, and 5.419% ash content. Meanwhile, at the compression pressure of 3000 psi charcoal briquettes have an average heating value of 6685.144 cal/g, 1.288% water content, and 6.627% ash content. Charcoal briquettes produced by varying the pressure of the briquetting press have met the quality standard of SNI 01-6235-2000 briquettes. The most optimum compression pressure for charcoal briquetting obtained in this study was 2000 psi.